Agents and multi-agent systems: technologies and applications 2021 - García-León, Ibza America; Pereda Beltrán, Noemi; Sotelo Moreno, Javier (Springer, 2021)
This article shows the analysis and design of the model and methodology of an Intelligent System for the Evaluation of Implicit Memory with Semantic Emotional Stimuli, the learning agent will be implemented on a mobile device, which will perform two tests (called phases) for girls who have suffered child victimization, taking into account the implicit memory in child victims of Child Sexual Abuse.
Intelligent system for the evaluation of implicit memory with semantic emotional stimuli (IS-EimSeS)
Keywords: Intelligent agent; Implicit memory; Data analysis; Semantic emotional stimuli; Campus Mexicali